ECMT (Electoral Campaign Management Training) manual. - Institute for Popular Democracy (Quezon City Institute for Popular Democracy, 2002)
A manual for the advancement of citizen agenda and good governance for national development and democratization.
Keywords: Campaign management -- Philippines -- Handbooks, manuals, etc; Elections -- Philippines; Philippines -- Politics and government